Konstruksi Sosial Kuasa Pengetahuan Zakat : Studi Kasus Lembaga Amil Zakat di Propinsi Jambi dan Sumatera Barat - Malik, Abdul; Hadi Dharmawan, Arya; Sumarti, Titik (Sodality: Jurnal Sosiologi Pedesaan, 2010)
The governances of zakat is important to be studied, especially about the dynamics of knowledge, rationality, and interest in zakat governance. This study focused on the battle of knowledge, rationality and conflicts of interest in zakat governance. The approach in this study is a qualitative approach with a methodology constructivism paradigm. The data obtained by phenomenology method with depth interview techniques and documentation. Data were analyzed using structural conflict perspective with Foucaultian style, especially the theory of power and knowledge. The results showed that: there are three spheres of knowledge, that competing to get authorities in the governance of zakat (religious knowledge, modern knowledge and local knowledge). The discourse of the governance of zakat in the LAZ of community was dominated by the religious knowledge and local knowledge, while at the Bazda and LAZ of Semen Padang, discourse is dominated by modern knowledge. Second, the rationality of LAZ of community is asceticism and altruism with the interests of individual piety and social piety, but the rationality of Bazda is developmentalism to achieve integration and uniformity, while the rationality of LAZ Semen Padang is maximize Utility, with profit interests and investment security. Finally, the phenomenon of zakat governances was showed as moral laundering efforts